Resistance to online banking : examination of resistance - Elvar Örn Hrafnsson 1986- (2018)
The number of bank branches in Europe have been declining in recent years, as the number of branches in Iceland have especially decreased. The reasons for this shift are partly due to the emergence of new innovations in the banking industry which allows consumers to service themselves mostly anywhere in the world, without having to set a foot in a bank. This thesis, which is a part of a collaboration with Íslandsbanki, sets out to examine the factors that explain the resistance to online banking. A questionnaire was submitted at different branches of Íslandsbanki and online, it based on the five resistance barriers identified by earlier literature. 468 participants partook in the survey. The results suggested that the utilitarian reinforcers, convenience and time saving are the most common reasons for adopting online banking. The non-adopters consisted of two groups: individuals that lack skills and knowledge or access to the internet and rejectors that will not adopt online banking unless they are forced to do so. Furthermore, the results showed that there was a significant difference between age groups and income levels in terms of their attitude and views towards online banking. Gender, marital status and education showed no significant difference. Finally, these findings will hopefully help Íslandsbanki to identify were the opportunities lay so it may provide them with an advantage in the future.